2006
DOI: 10.1007/s10578-006-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Humor and its Relationship to Coping, Defense Strategies, Psychological Distress, and Well-Being

Abstract: The HSQ appears to be a psychometrically sound and clinically useful measure to assess humor dimensions in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
76
2
37

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(128 citation statements)
references
References 57 publications
13
76
2
37
Order By: Relevance
“…Por outro lado, os rapazes da amostra utilizam mais frequentemente estratégias disfuncionais, seja pela utilização de drogas ou procura de humor. Enquanto a primeira estratégia, claramente disfuncional (Bermúdez et al, 2009;Frydenberg & Lewis, 1991;Rodríguez et al, 2012), a segunda pode estar associada a uma resolução mais positiva da situação desafiadora (Erickson & Feldstein, 2007;Merza et al, 2009).…”
Section: Discussionunclassified
“…Por outro lado, os rapazes da amostra utilizam mais frequentemente estratégias disfuncionais, seja pela utilização de drogas ou procura de humor. Enquanto a primeira estratégia, claramente disfuncional (Bermúdez et al, 2009;Frydenberg & Lewis, 1991;Rodríguez et al, 2012), a segunda pode estar associada a uma resolução mais positiva da situação desafiadora (Erickson & Feldstein, 2007;Merza et al, 2009).…”
Section: Discussionunclassified
“…de modo que una visión positiva sobre el futuro parece ser la tónica general de los jóvenes de nuestro país, aunque los cambios en la situación económica general puede que modifiquen esta perspectiva optimista global, En relación al Humor, los primeros estudios con niños y adolescentes están proporcionando información valiosa sobre las funciones cognitivas, sociales, defensivas y fisiológicas del mismo. Tal y como resumen a partir de la literatura Psy, Soc, & Educ, 2010, vol 2, Nº2 al respecto Erickson y Feldstein (2007), los niños con "buen sentido el humor" tienden a ser más asertivos y competentes en contextos sociales y académicos. Estos autores sugieren que el sentido del humor puede jugar un papel importante como estrategia de afrontamiento y defensiva en los adolescentes.…”
Section: Fortalezas Transcendentalesunclassified
“…In the mentioned population as many as 49% of the variability of the subjective well-being was explained by two humor styles -the self-enhancing (35% of the variability) and aggressive (14% variability; Tümkaya, 2011). Also, studies involving adolescents aged 12-15 years have shown that constructive humor styles are accompanied by better adaptation understood as satisfactory interpersonal relations (with peers and parents), a high self-esteem and self-reliance (Erickson & Feldstein, 2007). The aggressive and self-defeating humor styles went hand in hand with a worse adaptation revealing the level of well-being.…”
Section: Humor Correlates As a Positive Dispositionmentioning
confidence: 99%
“…also Ruch, 2008). According to Erickson and Feldstein (2007), both constructive humor styles -the affiliative and self-enhancing, can be treated as positive properties of an individual that are identical to character and/or virtue strengths.…”
mentioning
confidence: 99%
See 1 more Smart Citation